Les discours des manuels de philosophie en France et au Brésil : une analyse contrastive - Daniela Nienkötter Sardá (Corela)
The theme of this study is the comparison of discourses within French and Brazilian philosophy textbooks. Our purpose is to identify the representations of philosophy existing in a corpus composed of French and Brazilian textbooks through an interdisciplinary approach, that of discourse analysis or “comparative discourse linguistics”. First, we will consider the teaching context of this discipline in France and Brazil. Then, we will present some questions relative to the corpus as well as the interdisciplinary model adopted for its analysis, the descriptive and interpretive model (von Münchow, 2004). Some assumptions about the representations of philosophy that circulate in the French and Brazilian ethnolinguistic communities will be presented at the end of this article.